Comparison of different bone substitutes in the repair of rat calvaria critical size defects: questioning the need for alveolar ridge presentation - Theodoro, Letícia Helena [UNESP]; Campista, Christian Cezane Cardoso; Bury, Luiz Lordelo; Souza, Ricardo Guanaes Barbosa de; Muniz, Yuri Santos; Longo, Mariellen [UNESP]; Mulinari-Santos, Gabriel [UNESP]; Ervolino, Edilson [UNESP]; Levin, Liran; Garcia, Valdir Gouveia [UNESP] (Quintessence Publishing Co Inc, 2024)
Objective: This study aimed to evaluate the effectiveness of biomaterials in bone healing of critical bone defects created by piezoelectric surgery in rat calvaria. Method and materials: Histomorphologic analysis was performed to assess bone regeneration and tissue response. Fifty animals were randomized into five groups with one of the following treatments: Control group (n = 10), spontaneous blood clot formation with no bone fill; BO group (Bio-Oss, Geistlich Pharma; n = 10), defects were filled with bovine medullary bone substitute; BF group (Bonefill, Bionnovation; n = 10), defects were filled with bovine cortical bone substitute; hydroxyapatite group (n = 10), defects were filled with hydroxyapatite; calcium sulfate group (n = 10), defects were filled with calcium sulfate. Five animals from each group were euthanized at 30 and 45 days. The histomorphometry calculated the percentage of the new bone formation in the bone defect. Results: All data obtained were evaluated statistically consider-ing P < .05 as statistically significant. The results demonstrated the potential of all biomaterials for enhancing bone regenera-tion. The findings showed no statistical differences between all the biomaterials at 30 and 45 days including the control group without bone grafting. Conclusion: In conclusion, the tested bio-materials presented an estimated capacity of osteoconduction, statistically nonsignificant between them. In addition, the selec-tion of biomaterial should consider the specific clinical aspect, resorption rates, size of the particle, and desired bone healing responses. It is important to emphasize that in some cases, using no bone filler might provide comparable results with reduced cost and possible complications questioning the very frequent use of ridge presentation procedures. (Quintessence Int 2024;55:328-334; doi: 10.3290/ j.qi.b4955867)
Keywords: bone; bone substitutes; extraction; implants; wound healing